2012
DOI: 10.3126/jonmc.v1i1.7286
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and significance of iron deficiency of anaemia among people of Mornag District of Nepal

Abstract: Abstarct:Iron

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
2
2
0
Order By: Relevance
“…In our study, anemia was seen in 28.1% cases among 975 CBC samples run during the study period. Similar finding was seen in a study done in eastern part of Nepal by Sinha et al 12 where the prevalence of anemia was 25.6 % . Another study done in Nepal showed that the prevalence of anemia among school going children ranged from 31.6% to 45.3%.…”
Section: Fig 2: Age Wise Distributionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, anemia was seen in 28.1% cases among 975 CBC samples run during the study period. Similar finding was seen in a study done in eastern part of Nepal by Sinha et al 12 where the prevalence of anemia was 25.6 % . Another study done in Nepal showed that the prevalence of anemia among school going children ranged from 31.6% to 45.3%.…”
Section: Fig 2: Age Wise Distributionsupporting
confidence: 90%
“…[5][6][7][8][18][19][20] Studies done in Nepal shows that iron deficiency is very common and it is most commonly seen in females as well as children. 12,19,21 Macrocytic anemia was also quite common among older adults and comprises of almost 14% of all anemia cases. 20 Macrocytosis is the most commonly associated with vitamin B12, folic acid deficiency followed by alcoholism and liver disease.…”
Section: Fig 2: Age Wise Distributionmentioning
confidence: 99%
“…10 In a study done by Sinha et al among the people of Morang district of Nepal 25.57% of the patients were suffering from iron deficiency anemia. 11 In the present study it was seen that most of the patients (72 % ) had microcytic hypochromic blood picture. Patel et al and Mach-Pascual et al in their studies found microcytic hypochromic blood picture in 40% and 35.2% of anemic patients respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies conducted to analyse the factors associated with anaemia among WRA in Nepal have only explored a few specific individual and household factors (Chandyo et al, 2007; Gautam, Min, Kim, & Jeong, 2019; Harding, Aguayo, Namirembe, & Webb, 2018), and some are based on the analysis of a specific sample or subnational data (Baral & Onta, 2009; Mishra, Marasini, Gupta, Agrawal, & Gautam, 2018; Sinha, Majumdar, & Yadav, 2011). For instance, a study conducted by Gautam et al in 2019 (using 2016 Nepal Demographic and Health Survey [NDHS]) identified that source of drinking water, women's use of hormonal contraception, overweight/obesity and smoking status were significantly associated with anaemia (Gautam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%